Laparoscopic hysterectomy after concurrent radiochemotherapy in locally advanced cervical cancer compared to laparotomy: A multi institutional prospective pilot study of cost, surgical outcome and quality of life. Issue 3 (March 2016) - Baffert, S.; Alran, S.; Fourchotte, V.; Traore, M.A.; Simondi, C.; Mathevet, P.; Loustalot, C.; Binelli, C.; Jaffre, I.; Barranger, E.; Dupre, P.F.; Ferron, G.; et al.
Abstract: Objective: Laparoscopy allows hysterectomies after chemoradiation to be performed without opening the abdominal wall. We measured the costs and quality of life for locally advanced cervical cancer patients operated on via laparoscopy compared to laparotomy. Study design: We conducted an observational prospective multicenter study on locally advanced cervical cancer patients undergoing an extrafascial hysterectomy after concurrent chemoradiotherapy (CRT). We assessed the costs from the medical visit before surgery up to the first month after surgery from the providers' perspective and measured the quality of life using the EORTC QLQ-C30 and QLQ-CX24 up to six months. Results: Sixty two patients (39 laparoscopy and 23 laparotomy) from December 2008 to November 2011 were included. There was no difference in operative time, or intraoperative and post-operative complication rates between the two groups. Intraoperative transfusion and abdominal drain were significantly lower in the laparoscopy group (respectively, p = 0.04 and p < 0.01), as well as the duration of hospital stay (7.3 d vs 5.7 d, p < 0.001). All patients who underwent laparoscopic hysterectomy were discharged to home, whereas 4 laparotomy patients used convalescence homes (p = 0.01). Mean costs at one month were €10, 991 for laparotomy and €11, 267 for laparoscopy (p = 0.76). Sexual activity is better for the laparoscopy group at six months (p = 0.01). Conclusion: Laparoscopy for an extrafascial hysterectomy after CRT in locally advanced cervical cancer patients brought better quality of life with similar costs compared to laparotomy, and should therefore be the first choice for surgeons.